Vienan Karjalan asutushistoria nimistön valossa - Kuzmin, Denis (Helsingin yliopisto, 2014)
The dissertation investigates the settlement history of Russian Northern Karelia, i.e. White Sea Karelia (Vienan Karjala), in the light of onomastics. It consists of six articles based on linguistic material, most notably toponyms, anthroponyms, dialectal vocabulary and oral history. A considerable part of the research materials have been collected by the author in the course of field expeditions. The main methodology employed in the articles is the investigation of the spread of toponymic types in the Finnic languages. They bear witness to early population movements that cannot be investigated in the light of archaeology or historical documents. Particular toponymic models can be connected with the spread of the Karelian population from the Lake Ladoga region to the north. Other types provide evidence of a population that entered Northern Karelia from present-day Finland. Most notably, parallels in the toponymy of the Savo and Häme provinces and the area of White Sea Karelia can be found. The other main methodology used in the articles is the investigation of the substrate toponyms, i.e. analysis of toponyms that bear witness to language forms spoken earlier in a particular area. For instance, in White Sea Karelia, a notable amount of toponyms from Saami languages can be found. In the Russian-speaking White Sea coast area, in turn, a notable Finnic substrate from Karelian is discernable. Thus, there are grounds to suggest that the present linguistic areas of the investigated region have come to being relatively late and that as late as in the Middle Ages, the linguistic map of the region was considerably different. There is evidence to suggest that the Saami population in the area survived up to the 17th century. A further source of information in the dissertation is the oral history, i.e. stories and remembrances of the history of the Karelian settlements. Most of this material has never before been collected or investigated in the historical literature. Additionally, an analysis of the Karelian family names ...